Numerical Study and Comparison of the Settlement Behaviours of Axially Loaded Piles using Different Material Models. - Gowthaman, S.; Nasvi, M.C.M.; Krishnya, S. (The Institution of Engineers, Sri Lanka (IESL), 2017)
The settlement behaviour of axially loaded piles is one of the prime factors that control the design of single and group piles. Therefore, this research focused on the settlement behaviour of a pile foundation located in sandy-silt under the load of a high-rise building, by simulating it using PLAXIS numerical package and giving consideration to interface effects. Four different types of analysis were investigated: (i) a Linear Elastic (LE) analysis where the soil was assumed as linear-elastic; (ii) a simple Non Linear (NL) analysis where the soil was completely assumed as a Mohr-Coulomb(MC) model; (iii) Non Linear (NL) analysis where the soil was completely assumed as a Hardening -Soil (HS) model; and (iv) a combined (NL-LE and NL-NL) analysis assuming that the soil close to the pile shaft is a nonlinear model and that the soil in the remaining area is made of either linear material or simple nonlinear material (MC). The results of the analysis suggest that the complete MC model shows good agreement with the settlement behaviour obtained from field static load tests at lower working loads. However, the incorporation of a nonlinear HS interface zone of soil is required to predict the settlement at higher working loads. In addition, it was noted that an interface thickness that is twice the pile diameter with the remaining soil modelled as MC would suffice to ascertain the load transfer mechanism of a typical pile.
Keywords: Hardening-soil model.; Interface.; Linear-elastic.; Mohr-coulomb model.; Settlement.